Case report and discussion: Pre-implantation genetic diagnosis with surrogacy in vascular Ehlers–Danlos syndrome - Angwin, Chloe; Ghali, Neeti; Stephanie van Dijk, Fleur (Frontiers in Genetics, 2023)
Background Vascular Ehlers-Danlos Syndrome (vEDS) is an autosomal dominant inherited connective tissue condition, characterized by generalised tissue fragility with increased risk of arterial dissection and hollow organ rupture. For women with vEDS, pregnancy and childbirth carry significant risk of both morbidity and mortality. The Human Fertilisation and Embryology Authority has approved vEDS for pre-implantation genetic diagnosis (PGD) given the potential for life limiting complications. PGD avoids implantation of embryos that are affected by specific disorders by carrying out genetic testing (either for a familial variant or whole gene) and selecting unaffected embryos prior to implantation. Case We present an essential clinical update to the only published clinical case of a woman with vEDS undergoing PGD with surrogacy, initially through stimulated in-vitro fertilisation (IVF) and in-vitro maturation (IVM) and subsequently though natural IVF. Conclusion In our experience, a subset of women with vEDS do wish to have biological, unaffected children through PGD despite being aware of the risks of pregnancy and delivery. Given the clinical heterogeneity in vEDS, these women could be considered on a case-by-case basis for PGD. Controlled studies with comprehensive patient monitoring evaluating the safety of PGD are essential to equitable healthcare provision.